Дорвыжы: удмуртский героический эпос / Михаил Худяков - Худяков Михаил Георгиевич (Удмуртия, 2020)
Экземпляры: Ф. 1 (20210503) / Инвентарный номер: 48223 / Цена: 500.00 / Авт.знак: Х 98 / ГРНТИ: 17 / ББК: 82.3(2Рос=Удм)